Toluene alkylation with methanol to p-xylene over heteropoly acids supported by clay - Bokade, Vijay V.; Deshpande, Suvarna S.; Patil, R.; Jain, S.; Yadav, G. D. (Journal of Natural Gas Chemistry, 2007)
{The alkylation of toluene with methanol for the selective formation of p-xylene was systematically studied. Very few studies have been reported on the use of superacids such as heteropolyacids on cheap supports, such as clay. This article deals with the use of different heteropoly acids (HPAs), viz, Dodeca-Tungstophosphoric acid [
Keywords: co-crystalline; p-xylene; toluene alkylation; ZSM-12; ZSM-5

Transesterification of sunflower oil catalyzed by flyash-based solid catalysts - Kotwal, M. S.; Niphadkar, P. S.; Deshpande, Suvarna S.; Bokade, Vijay V.; Joshi, P. N. (Fuel, 2009)
Flyash-based base catalyst was used in the transesterification of sunflower oil with methanol to methyl esters in a heterogeneous manner. Catalyst preparation variables such as, the KNO(3) loading amount and calcination temperature were optimized. The catalysts were characterized by powder XRD. The catalyst prepared by loading of 5 wt.% KNO(3) on flyash followed by its calcination at 773 K has exhibited maximum oil conversion (87.5 wt.%). The influence of various reaction parameters such as % catalyst loading, methanol to oil molar ratio, reaction time, temperature, reusability of the catalyst on the catalytic activity was investigated. K(2)O derived from KNO(3) might be an essential component in the catalyst for its efficiency. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Flyash; heterogeneous catalyst; Methyl ester; Sunflower oil; transesterification